IMTA-Based Arabic Language Learning Curriculum at LKBA At-Tasniim Yogyakarta - Mitrajati, Kenyo; Musthofa, Tulus; Baroroh, R. Umi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze the Arabic language learning curriculum at the Foreign Language Course Institute (LKBA) At-Tasniim Yogyakarta with the perspective of IMTA' (al-Iţār al-Marji'ī' li Ta'līm al-Lugah al-'Arabiyyah). This research is qualitative with a literature approach. The research data is in the form of an Arabic language learning curriculum applied at the research site with the source of curriculum document data at LKBA At-Tasniim Yogyakarta. The data collection technique uses documentation. Meanwhile, data analysis uses content analysis. The study's results stated that the Arabic language learning curriculum at LKBA At-Tasniim Yogyakarta showed conformity with the level of IMTA's competency standards. This is marked by the goal of student competence at levels 1 to 3 at LKBA At-Tasniim Yogyakarta, which intersects with level 2 of IMTA'. The Arabic language learning curriculum at LKBA At-Tasniim Yogyakarta is designed to pay attention to gradually developing students' language skills from level 1 to level 3. In this case, there is a significant influence and slice with the level 2 IMTA level.